2016
DOI: 10.1093/gji/ggw377
|View full text |Cite
|
Sign up to set email alerts
|

The time dependence of rock healing as a universal relaxation process, a tutorial

Abstract: S U M M A R YThe material properties of earth materials often change after the material has been perturbed (slow dynamics). For example, the seismic velocity of subsurface materials changes after earthquakes, and granular materials compact after being shaken. Such relaxation processes are associated by observables that change logarithmically with time. Since the logarithm diverges for short and long times, the relaxation can, strictly speaking, not have a log-time dependence. We present a self-contained descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 85 publications
2
113
0
Order By: Relevance
“…A similar idea has been used to model the log time relaxation characteristic of the so‐called slow dynamics observed in many materials including rocks (Gibbs et al, ; TenCate et al, ; Zaitsev et al, , ). To illustrate the concept, Snieder et al () showed that summing individual relaxation functions with exponential Maxwell kinetics, f i ( t )=exp(‐ t / τ i )/ τ i , where τ i is the relaxation time, gives an aggregate relaxation function characterized by a long log( t ) behavior at intermediate times. One important feature of this model is that the duration of the log( t ) segment can be arbitrarily extended by increasing the range of relaxation times, that is, [ τ min , τ max ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar idea has been used to model the log time relaxation characteristic of the so‐called slow dynamics observed in many materials including rocks (Gibbs et al, ; TenCate et al, ; Zaitsev et al, , ). To illustrate the concept, Snieder et al () showed that summing individual relaxation functions with exponential Maxwell kinetics, f i ( t )=exp(‐ t / τ i )/ τ i , where τ i is the relaxation time, gives an aggregate relaxation function characterized by a long log( t ) behavior at intermediate times. One important feature of this model is that the duration of the log( t ) segment can be arbitrarily extended by increasing the range of relaxation times, that is, [ τ min , τ max ].…”
Section: Discussionmentioning
confidence: 99%
“…One important feature of this model is that the duration of the log( t ) segment can be arbitrarily extended by increasing the range of relaxation times, that is, [ τ min , τ max ]. In the same paper, Snieder et al () presented another illustrative model with no variations in relaxation time but which, nevertheless, produced approximate log( t ) kinetics. This model considers the time‐dependent closure of a rough fracture contained in a linear viscoelastic Kelvin material (dashpot and spring in parallel ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the strong ground motions, a relaxation process may follow as the grains rearrange themselves and/or cracks close as observed in rock samples during laboratory experiments (e.g., Johnson & Jia, ; Ten Cate & Shankland, ; TenCate et al, ) and in the shallow subsurface after earthquakes (Nakata & Snieder, ; Rubinstein & Beroza, ; Sawazaki et al, ; Schaff & Beroza, ). This relaxation process can be modeled through viscoelastic rheology as the medium progressively recovers to its preevent state (e.g., Hamiel et al, ; Lebedev & Ostrovsky, ; Lieou et al, ; Lyakhovsky, Ben‐Zion, & Agnon, ; Snieder et al, ). For extreme levels of strain, a pure plastic rheology better describes the material response, whereby a permanent and not recoverable deformation occurs.…”
Section: Introductionmentioning
confidence: 99%